Cambodia : 2018 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Cambodia. (IMF Staff Country Reports; Country Report ;, 2018)
Cambodia has made significant progress towards the Sustainable Development Goals (SDGs) due to years of impressive economic growth and reforms. Income growth has outpaced peers, poverty has declined, and the economy has begun to gradually diversify. At the same time, elevated financial sector vulnerabilities, development spending needs, and governance weaknesses pose challenges for further advancing sustainable growth and development.